Difference of ecological half-life and transfer coefficient in aquatic invertebrates between high and low radiocesium contaminated streams - Mayumi Yoshimura (Nature Portfolio, 2020)
Abstract The Fukushima accident emitted radioactive substances into the environment, contaminating litter, algae, sand substrate, aquatic invertebrates, and fish in freshwater streams. Because these substances have substantial effects on stream ecology over many years, it is necessary to clarify the diffusion and decay mechanisms of radiocesium. The transfer coefficient differed among aquatic invertebrate groups, likely due to the differences in habitat. The ecological half-life of cesium was longer where the air dose rate was lower. The transfer coefficient was also higher in areas with lower air dose rate. The radiocesium concentration in algae was inversely related to stream current velocity in the radiocesium-contaminated area. However, this relationship was not observed in the lower air dose rate area: the radiocesium concentration in algae in the rapid-velocity areas tended to be higher than that in the slow-velocity areas. This reverse trend would lead to a longer period of freshwater contamination. The radiocesium concentration would continue to decrease in highly contaminated areas, but it would be difficult to reduce the radiocesium concentration in less-contaminated areas because different contamination mechanisms are at work. Controlling the water flow is key to regulating radiocesium concentration in freshwater ecosystems.